2016
DOI: 10.25289/ml.2016.5.2.71
|View full text |Cite
|
Sign up to set email alerts
|

Use of Lasers in the Treatment of Alopecia Areata

Abstract: Alopecia areata (AA) is a complex autoimmune disease characterized by round or oval patches of non-scarring hair loss that is mediated by lymphocytes affecting the hair follicles. To treat localized AA, intralesional corticosteroid injections and topical corticosteroids are most commonly used, while for widespread AA, systemic steroids, immunosuppresants, and contact immunotherapy are commonly considered. However, therapeutic options for refractory AA that is unresponsive to these conventional treatments are l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
(60 reference statements)
0
5
0
Order By: Relevance
“…Further research is needed to understand how LLLT works and assess its efficacy in AA treatment. 64 , 65 The antihistamine, fexofenadine, has been found to be a helpful adjuvant therapeutic with contact immunotherapy in the treatment of atopic AA but not non-atopic AA. 66 , 67 …”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Further research is needed to understand how LLLT works and assess its efficacy in AA treatment. 64 , 65 The antihistamine, fexofenadine, has been found to be a helpful adjuvant therapeutic with contact immunotherapy in the treatment of atopic AA but not non-atopic AA. 66 , 67 …”
Section: Treatmentmentioning
confidence: 99%
“…Further research is needed to understand how LLLT works and assess its efficacy in AA treatment. 64,65 The antihistamine, fexofenadine, has been found to be a helpful adjuvant therapeutic with contact immunotherapy in the treatment of atopic AA but not non-atopic AA. 66,67 Other key factors aside from disease severity that may influence a clinician's choice of treatment include patientperceived disease severity, patient distress, and impact on the patient's social life.…”
Section: A Brief Review Of Prior Treatment Options For Alopecia Areatamentioning
confidence: 99%
“…Several studies have reported that LLLT is effective in various fields, including treatment of alopecia, 16 vestibulopathy, 17 and ophthalmic diseases. 18,19 However, the mechanism of LLLT has not been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…In transoral approach, after tonsillectomy, muscles and mucosa membranes are dissected to find the apex of the styloid process, which is then removed using a cutting tool (CO2 laser). [13][14][15][16][17][18] Transoral approach has a cosmetic advantage which leaves no visible scar after surgery, but also it has a disadvantage that the styloid process does not completely expose during the operation. 19 Recently, a new method was introduced in which the styloid process is removed after an incision is made into the anterior tonsil pillar and the tonsil is only pushed to the medial side without performing tonsillectomy.…”
Section: Discussionmentioning
confidence: 99%